ASPEK SOSIAL BUDAYA JAWA DALAM NOVEL PARA PRIYAYI KARYA UMAR KAYAM: KAJIAN SOSIOLOGI SASTRA - Renita Renita; Yasnur Asri; Zulfadhli Zulfadhli (Jurnal Bahasa dan Sastra, 2013)
The  purpose of this research is to describe the social aspects which are included:  (1) the main aspects in family, (2) aspects of atiquette or manners, (3) aspects of harmony, and the social system in the novel of  Para Priyayi which  is made by  Umar Kayam. This data is collected by reading and marking. Texts which is dedicated to same social and cultural aspects of javanese some parts of the novel which have been marked and thend. Being taken by using date of inventariaton the steps which conducted in analysing data are, (1) collecting data as a social aspect of Javanese culture, (2) calssification as a using teory, data collecting and classification by using taking note of the happenings which is connected whit a social aspect which is seen from a social problem, (3)  clasifing data  based teory  the reference, (4) conclude the date description in the form of writing report.